Drought resistance of introdused nectarine varieties (Prunus persica (L.) Batsch subsp. nucipersica Dipp.) in the conditions of South Coast of the Crimea - Т. В. Шишова (Plant Varieties Studying and Protection)
The studying results of drought resistance for introdused nectarine varieties in the conditions of South Coast of the Crimea have been given. Four varieties shoved high resistance to drought conditions during two years have been selected.